1960
DOI: 10.1113/jphysiol.1960.sp006395
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between motoneurones and muscles in respect of the characteristic speeds of their responses

Abstract: In the preceding paper (Buller, Eccles & Eccles, 1960) evidence was presented which suggested that the differentiation of slow muscles of the cat hind limb to a large extent failed to occur after certain operative procedures on the spinal cord. This finding indicates that in some way the central nervous system controls muscle differentiation. A more analytic investigation into this postulated influence of nerve on muscle has been accomplished by dividing and cross-uniting nerves to fast and slow muscles, so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
419
4
5

Year Published

1962
1962
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,033 publications
(454 citation statements)
references
References 30 publications
26
419
4
5
Order By: Relevance
“…These and other biochemical characteristics are known to be regulated by the functional demands imposed on the muscle by means of its innervation (e.g., Buller et al, 1960;Vrbova et al, 1978). Implicit in the idea originally formulated by Sherrington (1925), that the motor unit forms the smallest functional component of skeletal muscle controlled by the nervous system, is the concept of biochemical uniformity among the unit's muscle fibers.…”
mentioning
confidence: 99%
“…These and other biochemical characteristics are known to be regulated by the functional demands imposed on the muscle by means of its innervation (e.g., Buller et al, 1960;Vrbova et al, 1978). Implicit in the idea originally formulated by Sherrington (1925), that the motor unit forms the smallest functional component of skeletal muscle controlled by the nervous system, is the concept of biochemical uniformity among the unit's muscle fibers.…”
mentioning
confidence: 99%
“…The cross-rernnervation experiments of Buller et al (1960) and others (Buller et al, 1969;Close, 1969;Bagust et al, 1981;Chan et al, 1982) demonstrated that the motoneuron regulates a variety of contractile, biochemical, and histochemical properties of skeletal muscle. The signals responsible for this muscular plasticity were hypothesized to derive from newly directed activity patterns and/or the supply of a neurotrophic substance to the muscle by the innervating nerve (Buller et al, 1960).…”
mentioning
confidence: 99%
“…The signals responsible for this muscular plasticity were hypothesized to derive from newly directed activity patterns and/or the supply of a neurotrophic substance to the muscle by the innervating nerve (Buller et al, 1960).…”
mentioning
confidence: 99%
“…Alternatively, innervation of targets by nerves with properties different from those of the normal afferent can lead to functional and biochemical modifications in the postsynaptic target (Buller et al, 1960;Streter et al, 1975;reviewed in Close, 1969). While these findings suggest that synaptic inputs play a crucial role in shaping and maintaining target structures, they do not indicate what signals underlie these regulatory properties.…”
mentioning
confidence: 99%